Colombia : Staff Report for the 2002 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Colombia's 2002 Article IV Consultation and Request for Stand-By Arrangement. The economic situation worsened in the first half of 2002. Economic activity has remained sluggish, and the fiscal consolidation has gone off-track. Exacerbated by increased contagion from other countries in the region, concerns about fiscal solvency led to increased pressure on the peso from mid-year and a loss of external market access. Executive Directors have commended the new government's swift and comprehensive action to face a difficult domestic and external situation.